Kepemimpinan Lurah Dalam Meningkatkan Kinerja Pegawai di Kantor Kelurahan Bolihuangga - Bahuwa, Moh. Hafiz; Ilato, Rosman; Aneta, Yanti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to determine and describe the Village Head's Leadership in Improving Employee Performance at the Bolihuangga Subdistrict Office, Limboto District, Gorontalo Regency. The data collection techniques used are observation, interviews and documentation. Based on the results of field research, the Village Head's Leadership in Improving Employee Performance at the Bolihuangga Village Office, Limboto District, Gorontalo Regency. Viewed from the aspects of Leadership as an Innovator, Leadership as a Communicator, Leadership as a Motivator, and Leadership as a Controller. There are still problems found, including, firstly, Leadership as an Innovator, where the Bolihuangga Village Head has not been able to create and provide innovation to employees at work, and the Bolihuangga Village Head is still lacking in encouraging his employees to create new things to improve performance, this causes The lack of creativity in work and innovation development in the Bolihuangga sub-district office, such as the condition of the rooms in the Bolihuangga sub-district office which are unstable and not neatly arranged. Secondly, Leadership as a Controller still lacks supervision from a village head as a leader which results in decreased employee performance which can be seen from the inaccuracy of entry times and work which is often postponed by employees.